2021
DOI: 10.3390/diagnostics11040712
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability as Measured by Thrombelastography May Be Associated with the Size of Acute Ischemic Infarct—A Pilot Study

Abstract: Background: Thromboelastography (TEG®) measures coagulation function in venous blood. Previous studies have reported that this device providing an integrated data on dynamics of clot formation may be useful for predicting clinical outcome in ischemic stroke. We investigated whether a hypercoagulability detected by thrombelastography may be associated with larger size of acute ischemic infarct. Methods: We included 40 ischemic stroke subjects with large artery atherosclerosis or small-vessel disease to a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…A common haemostatic assay used in clinical settings to manage and treat patients and predict patient outcomes is thromboelastography (TEG) [ 59 , 60 , 61 , 62 ]. TEG is extremely useful for measuring blood coagulation parameters as a myriad of aspects are ascertained simultaneously, including amplitude (A) (strength of the clot) and reaction time (R) (time until clot formation), thus aiding in the diagnosis and treatment of patients admitted to hospital with coagulopathy.…”
Section: Introductionmentioning
confidence: 99%
“…A common haemostatic assay used in clinical settings to manage and treat patients and predict patient outcomes is thromboelastography (TEG) [ 59 , 60 , 61 , 62 ]. TEG is extremely useful for measuring blood coagulation parameters as a myriad of aspects are ascertained simultaneously, including amplitude (A) (strength of the clot) and reaction time (R) (time until clot formation), thus aiding in the diagnosis and treatment of patients admitted to hospital with coagulopathy.…”
Section: Introductionmentioning
confidence: 99%
“…We also predicted whether patients would have a higher risk of adverse events. [15,16] Shimei et al [17] showed that the levels of TEG-related indicators in ACI patients were higher or lower than those in healthy controls, and with the severity of the disease. Logistic regression analysis confirmed that the relevant indicators of TEG were important risk factors affecting the degree of brain injury in patients with cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“… 53 In a cross-sectional, single-center study, higher MA and bigger α were associated with a larger size of ischemic infarct in the large artery atherosclerosis group. 55 …”
Section: The Application Of Teg In Aismentioning
confidence: 99%
“…53 In a cross-sectional, single-center study, higher MA and bigger α were associated with a larger size of ischemic infarct in the large artery atherosclerosis group. 55 Moreover, AIS is the most common neurologic complication of coronavirus disease 2019 (COVID-19). 56,57 The incidence of AIS induced by COVID-19 ranges only from 1% to 6%, but the motility rate of 38% is relatively high.…”
Section: Disease Monitoring In Aismentioning
confidence: 99%